Pengaruh Variasi Produk, Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Hop Hop Bubble Drink (Studi Kasus Mal Kota Kasablanka, Jakarta) - Fani Fadilah; Mariah (UNIVERSITAS KALBIS, 2022)
This study aims to see the effect of product influence, product quality and service quality on customer satisfaction of Hop Hop bubble drink in Casablanca City. There are three independent variables in this study, namely product variation, product quality and service quality, and one customer satisfaction variable. Researchers used quantitative methods and the sample used in this study was 130 respondents who had purchased the Hop bubble drink Mal Kota Kasablanka, Jakarta. The technique used in this research is purposive sampling which is part of the non-probability sampling. Data were analyzed by SPSS 22.0, with the results showing that the research variables that affect customer satisfaction of Hop Hop bubble drinks, product quality that affect customer satisfaction of Hop Hop bubble drinks, service quality that affect customer satisfaction of Hop Hop bubble drinks and product variations, quality product quality and service quality have a joint effect on customer satisfaction of Hop Hop bubble drink.